Features of the visual perception process: lexicographic aspect - Peredrienko, Tatiana Yu (Tyumen State University Herald. Humanities Research. Humanitates, 2023)
This paper delves into the phenomenon of perception and the importance of analyzing a person’s interaction with the world. The study focuses on the visual perception as the primary channel for obtaining information. The objective is to identify the characteristics of visual perception, as verbalized through lexical and phraseological units in the Russian language. The researcher has analyzed 118 lexical and phraseological units that nominate visual perception. By examining dictionary entries of perceptual verbs and phraseological units, she has formed synonymous rows that share a common concretizing seme, which names the features of the process of visual perception. Certain verbs are included in multiple synonymous rows, their polysemy result in the actualization of several features. This can cause the boundaries within the field to become blurred. The core position is characterized by the feature of purposefulness, which refers to the subject’s orientation towards the object of perception. The closest feature to the core is effectiveness, which signifies the end of the process with a positive or negative result. Duration is associated with effectiveness and implies fixation on the object of perception for a certain period. The next feature is assessment, which expresses the subject’s attitude towards the object. Finally, on the periphery, there is unreality of visual perception, where the image is based on existing experience rather than the real object. This language model effectively represents the features of visual perception, making it accessible, informative, and complete.